INTERNALISASI NILAI RELIGIUSITAS PADA SISWA MTSN 5 GODEAN SLEMAN YOGYAKARTA MELALUI PERINGATAN TAHUN BARU HIJRIYAH - Hidayatullah Hidayatullah; Andhina Ika Sunardi; Himawan Agung Nugroho (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2023)
This community service activity involves religious counseling to MTsN Godean Sleman Yogyakarta Sleman Yogyakarta students. This effort aims to introduce religious values ​​to students as part of the character education method emphasized by the government, especially in the midst of increasing incidents of juvenile delinquency. The focus of this service program is to provide education about the history of the Hijrah event of the Prophet Muhammad SAW to students. Various methods are used in this program, including observation, outreach, evaluation, and lectures. This activity took place at Madrasah Tsanawiyah Negeri 5 Godean Sleman Yogyakarta. The results of this activity show that students gain motivation and enthusiasm to follow in the footsteps of the Hijrah inspired by the Prophet Muhammad SAW. Apart from that, this program also provides understanding and knowledge about the events of the Hijrah of the Prophet Muhammad from Makkah to Medina, which some MTsN Godean Sleman Yogyakarta Sleman Yogyakarta students may not have previously known.